Laimosemion leticia (Teleostei: Cyprinodontiformes: Rivulidae), a new species from the upper Rio Amazonas, Southern Colombia - Valdesalici, Stefano (Zootaxa, 2016)
Laimosemion leticia is described from the Rio Tacana drainage, upper Rio Amazonas basin, Southern Colombia. The new species was found in a shallow swamp within a tropical rainforest in the vicinity of Leticia, capital of the department of Amazonas and southernmost municipality of Colombia. This miniature species is considered to be a member of the Owiyeye subgenus, which is diagnosed by a unique frontal squamation. Laimosemion leticia can be distinguished from all other species of the genus by the unique colour pattern on the unpaired fins. The new species appears related to L. jauaperi, L. uatuman and L. ubim due to the similar flank colour pattern in males, but is easy distinguished by coloration of the unpaired fins and morphological characters.